A new annual killifish, Moema beltramonorum (Cyprinodontiformes: Rivulidae) from the Amazon basin, Bolivia - Valdesalici, Stefano (Zootaxa, 2023)
A new annual killifish species, Moema beltramonorum, is described from a seasonal swamp next to arroyo Crespo, belonging to Río San Martin, a tributary of Río Iténez, Amazon River basin, Bolivia. The new taxon presents an unique combination of male colour pattern characters not present in any congener, and an unique caudal fin coloration.